Evaluation of intraoperative magnetic resonance imaging/ultrasound fusion optimization for low-dose-rate prostate brachytherapy - Abel, Stephen; Renz, Paul; Gayou, Olivier; Tang, Jie; Werts, E. Day; Trombetta, Mark (Journal of Contemporary Brachytherapy, 2017)
Purpose: Intraoperative planning with transrectal ultrasound (US) is used for accurate seed placement and optimal dosimetry in prostate brachytherapy. However, prostate magnetic resonance imaging (MRI) has shown superiority in delineation of prostate anatomy. Accordingly, MRI/US fusion may be useful for accurate intraoperative planning. We analyzed planning with MRI/US fusion to compare differences in dosimetry and volume to that derived from the postoperative computed tomography (CT). Material and methods: Twenty patients underwent preoperative prostate MRI, which was fused intraoperatively with US during prostate brachytherapy. Intraoperative 125I or 103Pd seed placement was modified by the use of MRI fusion when indicated. Following implantation, dose comparisons were made between data derived from MRI/US and that from post-operative CT scans. Plan parameters analyzed included the D90 (dose to 90% of the prostate), rectal D30, V30 (volume of the rectum receiving 30 percent of dose), and prostate V100. Results: The median number of seeds implanted per patient was seventy-six. The MRI measured prostate volume, which was on average 4.47 cc larger than the CT measured prostate volume. In 9 patients, the apex of the prostate was better identified under MRI with the fusion protocol, and an average of 4 fewer seeds were required to be placed in the apex/urinary sphincter region. Both MRI and US individually showed a reduced intraoperative prostate D90 in comparison to the postoperative CT, with a larger mean difference for MRI in comparison with US (9.71 vs. 4.31 Gy, p = 0.007). This was also true for the prostate V100 (5.18 vs. 2.73 cc, p = 0.009). Post-operative CT underestimated rectal D30 and V30 in comparison to both MRI and US with MRI showing a larger mean difference than US for D30 (40.64 vs. 35.92 Gy, p = 0.04) and V30 (50.20 vs. 44.38 cc, p = 0.009). Conclusions: The MRI/US fusion demonstrated greater prostate volume compared to standard CT/US based planning likely due to the better resolution of the prostate apex. Furthermore, rectal dose was underestimated with CT vs. MRI based planning. Additional study is required to assess long-term clinical implications of disease control and effects on long-term toxicity, especially as related to the rectum and urinary sphincter. MRI/US intraoperative fusion may improve prostate dosimetry while sparing the rectum and urethra, potentially impacting disease control and late toxicity.